Nanoparticles obtained by confined impinging jet mixer: poly(lactide-co-glycolide) vs. Poly-ε-caprolactone - Turino, Ludmila Noelia (2018)
This paper is focused on the production and characterization of polymeric nanoparticles obtained by nanoprecipitation. The method consisted of using a confined impinging jet mixer (CIJM), circumventing high-energy equipment. Differences between the use of poly-ε-caprolactone (PCL) and poly(lactide-co-glycolide) (PLGA) as concerns particle mean size, zeta potential, and broad-spectrum antibiotic florfenicol entrapment were investigated. Other analyzed variables were polymer concentration, solvent, and anti-solvent flow rates, and antibiotic initial concentration. To our knowledge, no data were found related to PLGA and PCL nanoparticles comparison using CIJM. Also, florfenicol encapsulation within PCL or PLGA nanoparticles by nanoprecipitation has not been reported yet. The complexity of the nanoprecipitation phenomena has been confirmed, with many relevant variables involved in particles formation. PLGA resulted in smaller and more stable nanoparticles with higher entrapping of florfenicol than PCL.